Pengembangan E-LKPD Berbasis Multirepresentasi Berbantuan Liveworksheet pada Materi Hukum Newton - M Furqon; Suharli A.J.; Rahma Dani; Jeliana Veronika Sirait; Rindy Puspita Anggrini; Mely Chelvina Harahap; M. Fadhil Raga Ananda; Reva Dwi Kiranti (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2025)
This study is a research and development (R&D) project aimed at producing a multirepresentation-based electronic worksheet (E-LKPD) assisted by Liveworksheet on Newton's Law material that is both valid and practical for use in high school physics learning. The development model employed utilizes the initial three phases of ADDIE, namely Analysis, Design, and Development. The research findings demonstrate that the developed E-LKPD product falls within the category of highly valid and highly practical, with an Aiken's V validity index of 0.852, classified as excellent or highly valid, and a practicality level of 85.95%. The multirepresentation approach facilitates students' understanding of Newton's Law concepts through various forms of representation, including verbal, visual, mathematical, and diagrammatic representations. Furthermore, the interactive features embedded in Liveworksheet provide immediate feedback that supports students in learning independently and reflectively. Overall, this E-LKPD is valid and practical so that deemed suitable for use as an innovative learning medium and is expected to enhance students' conceptual understanding and higher-order thinking skills.